METACOPINA (OSTRACODA) DEL HETIANGIANO SUPERIOR EN EL SUDOESTE DE LA PROVINCIA DE MENDOZA, ARGENTINA (Ameghiniana, 2013)
Lower Jurassic Ostracoda are described for the first time from the northem bank of the Atuel river in the Province of Mendoza, Argentina. The monotypic occurrence here of Ogmoconchella ellipsoidea (Jones) is important since this species is common in the Hettangian-Iowermost Sinemurian interval in central West Europe. Ammonites from the same levels confirm the late Hettangian age of the deposit. These are Ihe oldest Jurassic ostracods yet recorded from Argentina. Dark colouration of the caparace is caused by the presence of pyrite.